Neptunium sorption and redox speciation at the illite surface under highly saline conditions. (15th October 2017) - Banik, Nidhu Lal; Marsac, Rémi; Lützenkirchen, Johannes; Marquardt, Christian Michael; Dardenne, Kathy; Rothe, Joerg; Bender, Kerstin; Geckeis, Horst
Abstract: Neptunium (Np) uptake on illite is investigated in 1 and 3.2 molal (m) NaCl solutions under inert (Ar) atmosphere for 4 < pHm < 10 (pHm = −log m H + ) and 5 × 10 −8 < [Np(V)]tot < 3 × 10 −4 M. In agreement with a previous study in 0.1 m NaCl solutions (Marsac et al., 2015a), Np(V) is the prevailing oxidation state in the aqueous solution, but Np uptake by illite is affected by surface induced reduction. The extent of Np(V) reduction to Np(IV) follows the measured redox potential (or the pe = −log ae− ), which is influenced by the introduced Np(V) amount, because of the low redox capacity of the illite. The presence of Np(IV) on the solid phase is verified by X-ray Absorption Near Edge Spectroscopy (XANES). We can conclude that Np uptake by illite is not significantly affected by the variation of m NaCl from 0.1 to 3.2 m and thus is in agreement with reports on tetravalent actinide and Np(V) sorption to clays at high ionic strength. The combination of (i) the two site protolysis non-electrostatic surface complexation and cation exchange model, (ii) the specific ion interaction theory to calculate activity coefficients for dissolved species and (iii) by accounting for redox equilibria and the stability of surface Np species, the overall Np uptake by illite can be simulated as a function of pHm, pe and m NaCl using a single set of parameters. The present experimental and modeling results are particularly important in the context of deep geological nuclear waste disposal since many sedimentary rocks or clay formations that are deemed suitable for this purpose exhibit highly saline porewaters.